Decolonizing the past: Integrating the 'practical past' and local literature in Southeast Asian primary history education - Farid, Mujahidin; Aji, Styo Mahendra Wasita (Priviet Social Sciences Journal, 2025)
The​‍​‌‍​‍‌ history curriculum in primary schools across Southeast Asia frequently continues to be the inheritance of colonialism, which means that it is dominated by a Western-derived, evidence-based "historical past" that largely disregards local narratives and ways of knowing. This​‍​‌‍​‍‌ article argues for the decolonization of history through the deliberate application of Michael Oakeshott's concept of the "practical past" and the use of regional and local literature. The present study, through a systematic review of the literature, shows that the dominant "historical past" model not only structures but also deepens the dependence of the knowledge system from which it originates. Therefore, it explores literary works to liberate the local people, such as historical novels, folktales, and legends, as authentic and reliable sources of community identity, core values, and "practical" historical knowledge. The findings show that such a blend results in a social change pedagogy that makes the class a dialogical space for the teacher's knowledge delivery and historical ​‍​‌‍​‍‌deliberation. Students' historical empathy, critical multimedia literacy, and deep bond with their cultural heritage are some of the outcomes of this approach. However, there are still many issues, such as the lack of teacher preparedness, the conflict between fact and meaning in the curriculum, and the limitations of standardized testing. The article posits that the "decolonial" strategy, which accords the "practical past" equal ontological and epistemological status with other aspects, does not mean the abandonment of academic rigor but rather its enhancement. This, in turn, facilitates the development of a pluriversal historical consciousness, which is a prerequisite for the formation of identity-secure and critically engaged future generations in Southeast ​‍​‌‍​‍‌Asia.